Diplopia, Convergent Strabismus, and Eye Abduction Palsy in a 12-Year-Old Boy with Autoimmune Thyroiditis - Pedro Marques; Sandra Jacinto; Maria do Carmo Pinto; Catarina Limbert; Lurdes Lopes (Case Reports in Pediatrics)
Pseudotumor cerebri (PTC) is defined by clinical criteria of increased intracranial pressure, elevated intracranial pressure with normal cerebrospinal fluid (CSF) composition, and exclusion of other causes such tumors, vascular abnormalities, or infections. The association of PTC with levothyroxine (LT4) has been reported. A 12-year-old boy has been followed up for autoimmune thyroiditis under LT4. Family history was irrelevant for endocrine or autoimmune diseases. A TSH level of 4.43 μUI/mL (0.39–3.10) motivated a LT4 adjustment from 75 to 88 μg/day. Five weeks later, he developed horizontal diplopia, convergent strabismus with left eye abduction palsy, and papilledema. Laboratorial evaluation revealed elevated free thyroxine level (1.05 ng/dL [0.65–1.01]) and low TSH, without other alterations. Lumbar puncture was performed and CSF opening pressure was 24 cm H2O with normal composition. Blood and CSF cultures were sterile. Brain MRI was normal. LT4 was temporarily discontinued and progressive improvement was observed, with a normal fundoscopy at day 10 and reversion of diplopia one month later. LT4 was restarted at lower dose and gradually titrated. The boy is currently asymptomatic. This case discloses the potential role of LT4 in inducing PTC. Despite its rarity and unclear association, PTC must be seen as a potential complication of LT4, after excluding all other intracranial hypertension causes.